The Expression of Netrin-1 in the Thymus and Its Effects on Thymocyte Adhesion and Migration - Xiao-Kai Guo; Yuan-Feng Liu; Yu Zhou; Xiu-Yuan Sun; Xiao-Ping Qian; Yu Zhang; Jun Zhang (Clinical and Developmental Immunology)
Netrin-1, a known axon guidance molecule, being a secreted laminin-related molecule, has been suggested to be involved in multiple physiological and pathological conditions, such as organogenesis, angiogenesis, tumorigenesis, and inflammation-mediated tissue injury. However, its function in thymocyte development is still unknown. Here, we demonstrate that Netrin-1 is expressed in mouse thymus tissue and is primarily expressed in thymic stromal cells, and the expression of Netrin-1 in thymocytes can be induced by anti-CD3 antibody or IL-7 treatment. Importantly, Netrin-1 mediates the adhesion of thymocytes, and this effect is comparable to or greater than that of fibronectin. Furthermore, Netrin-1 specifically promotes the chemotaxis of CXCL12. These suggest that Netrin-1 may play an important role in thymocyte development.